NUTRITIONAL STATUS RELATION TOWARD DEVELOPMENT OF NEURODEVELOPMENTAL TO INFANTS AGED 0-6 MONTHS WHO RECEIVED BREAST MILK EXCLUSIVELY AND NONEXCLUSIVELY (IN PUSKESMAS KEDUNGKANDANG MALANG) - Ida, Brigitta; Nugroho, Fajar Ari; Arysanthi, Inke Triana (Malang Neurology Journal, 2016)
Background. Breastfeeding is an important activity to maintain and prepare the next generation in the future. The low of exclusive breastfeeding at the family is one of the triggers for low of nutritional status and it associated with neurodevelopmental delays of infants.Objective. To identify and analyze the correlation of nutritional status on neurodevelopmental development in infants aged 0-6 months who are exclusive and non-exclusive breastfeeding in Kedungkandang Health Center Malang.Methods. An observational analytic using a cross-sectional approach . The samples were taken by Consecutive Sampling technique. Data were analyzed by Spearman Rank correlation test.Results. There is a significant correlation between nutritional status with neurodevelopmental development in infants aged 0-6 months with significance value p = 0.000 ( 0.000 < 0.05 ) and the strength of correlation (r=0,552) is medium.Conclusion. There is a positive correlation between nutritional status with neurodevelopmental progress of infants aged 0-6 months who are exclusively breastfed . Exclusive breastfeeding affects the nutritional status better, then a good nutritional status affected neurodevelopmental development also better.